Size-dependent policies and efficient firm creation - Sakai Ando (Osaka University, Institute of Social and Economic Research (ISER), 2018)
I study the welfare implications of size-dependent firm regulation policies (SDPs) in the presence of entrepreneurial risks. Although SDP has been considered a source of misallocation, I show that, once entrepreneurial risks are taken into account, SDP can improve efficiency. Quantitatively, I show that, based on French data, removing the SDP leads to output and welfare loss by 1.5% and 1.3%, respectively, in opposition to the output gain reported by the previous literature that abstracts from risks. Qualitatively, I solve an optimal non-linear SDP problem and show that the observed SDP shares certain features with the optimal SDP. The analysis uncovers a novel tradeoff between the inefficiencies of the intensive and extensive margins. In extension, it is shown that (1) whether SDPs improve efficiency depends on the level of financial development and (2) capital accumulation and consumption-smoothing motive further justify SDPs.
Keywords: D52; D61; H21; J08; L11; L24; L51; 330; misallocation; firm creation; size-dependent policy; financial development; incomplete markets